The combination use of inclisiran and statins versus statins alone in the treatment of dyslipidemia in mainland China: a cost-effectiveness analysis - Zhou, Wenjing; Liang, Zhuoru; Lou, Xiaohuan; Wang, Nansong; Liu, Xinyu; Li, Ruoxi; Pai, Pearl (Frontiers in Pharmacology, 2024)
Objective: Statin is well established as a classical lipid-lowering drugs and its cost has reduced considerably in the past years. Inclisiran is a new and effective lipid-lowering drug given as a subcutaneous injection at 6 monthly interval. This study aims to evaluate the cost-effectiveness of Inclisiran and statin versus statin alone for dyslipidemia in the China mainland population.The Markov decision-making model was used, and the clinical data and real-world data was collected at the University of Hong Kong-Shenzhen Hospital. Patients with cardiovascular disease (CVD) and blood lipid level above target on statin therapy were included as the target population, and analyzed for cardiovascular events, future medical expenses, and calculation made for total life cost, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios (ICERs). Sensitivity analysis was conducted to evaluate the influence of parameter uncertainty on the base-case analysis results.Results: If Inclisiran was priced at RMB 20,000.00 (USD 2973.49) per injection, patients in the Inclisiran and statin group would incur an incremental cost of RMB 449,233.56 (USD 66,789.60) compared with the statin group, and obtain 0.21 more QALYs in the whole life cycle. The subsequent ICER of RMB 2,127,756.78 (USD 316,343.32)/QALY, was significantly higher than the WTP threshold of 3 times China's per capita GDP which was RMB257,094.00 (USD 38,223.33) /QALY, suggesting that combined use of Inclisiran and statin was not cost-effective. If the price of Inclisiran were reduced to RMB 2,500.00 (USD 371.69)/injection, the ICER of patients in the Inclisiran and statin group would become RMB 257,790.63 (USD 38,326.91)/QALY, slightly lower than the WTP threshold of 3 times the per capita GDP of China, indicating that the combined use of Inclisiran and statin would be cost-effective..Inclisiran is priced at RMB 20,000.00 (USD 2973.49)/injection, then the combined use of Inclisiran and statins is not cost-effective compared with statin alone. It will be economical only if the price of Inclisiran is reduced by more than 88%.